KONSTRUKSI HUKUM PEMBERIAN KUASA PENGELOLAAN JALAN TOL (STUDI KASUS JALAN TOL SURABAYA-GRES|K) - , Maria Magdalena Edi Hardani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research on construction law granting authority of the highway management ( study case of the highway Surabaya - Gresik) is to aim to know whether the granting authority in the management of the highway Surabaya â Gresik can be constructed as Join Operational Agreement and juridical implication for granting such authority. To acquire the data research did with library research and field research. Respondent of this study is the giver of power and the power of two receivers. The conclution of this research showed that the agreement of the giver power to give the authority to receiver power. Together with the giver power to manage the highway by build a new business entity. There is a consession for 25 years to manage the highway before given to the authority holder.